The Contagion of Misgovernance in Nigeria: Reflections on the Influence of Non-Administrative Criteria - Nanji Rimdan Umoh; Adakai Filicus Amayah; Chiedozie Okechukwu Okafor; Elizabeth Aishatu Bature (PanAfrican Journal of Governance and Development, 2023)
Successive governments in Nigeria have failed to curtail the downward spiral of the sectors of her economy. The deepening socio-economic and political crises are assessed as occasioned by the dysfunctionality of the arms of government that jeopardizes essential service delivery to the detriment of the polity at whose behest they occupy the public offices. Despite the changes and institution of new administrative leadership through democratic processes, the quality of governance continues to dwindle. Poor policy formulation, implementing non-target-specific measures to deal with the malaises bedeviling the economy, and/or outright government inaction define the practical realities of Nigeria’s sociopolitical landscape. These plausible facts have driven wedges between the elected representatives in government and the polity who bear the brunt of the leadership failures in all spheres. The study determined whether a contagion effect birthed by non-administrative criteria underlies the transcendently perpetual misgovernance pervading the sectors of Nigeria’s economy. The study evaluates the influences of these criteria on the individuals, the potency of ‘group’ membership and sentiments, the contexts of leadership, and the implications for the trajectory of governance. With prioritization over the desired state of affairs in the country despite leadership changes and successive governments, these group memberships and sentiments remain inimically parallel to target-specific policy-making and de-emphasize national growth and development. The paper relies on the postulations of the social contagion theory of collective behavior and Riggs' assertions on non-administrative criteria in prismatic societies in assessing the misgovernance in Nigeria. A semi-structured Contagion in Leadership (CiL) e-questionnaire was designed to evaluate the influence of social contagion on the members of the arms of government and, consequently, on the quality of governance and service delivery in Nigeria’s Fourth Republic. It was disseminated on two social media platforms - WhatsApp and Twitter, for a wider reach. Two hundred ten (210) responses were recorded across an age range of 18 and 65+ years, with a mean age of 42. Strategies for enhancing the quality of governance, including entrenching constitutionalism, and engendering the responsibility of political officeholders toward policy actions, are proffered.